English Student Teachers’ Preparedness to Utilize Quizizz as a Learning Evaluation Tool in Differentiated Instruction Context - Syafa’ah, Nur (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
This study investigates the preparedness of English student teachers employing Quizizz as a digital assessment tool within the context of differentiated instruction. In a technology-driven educational environment, Quizizz provides a flexible platform for both formative and summative assessments, addressing diverse student needs and learning styles. This study collected the data through questionnaires, interviews, and classroom observations focused on student teachers’ experiences, perceptions, and challenges in integrating Quizizz into differentiated learning environments. The study's findings revealed a wide range of student teachers’ preparedness, with varying confidence levels of participants on how to use Quizizz influenced by their own knowledge, pedagogical background, and understanding of differentiated instruction principles. From the study, specific training program for incorporating technology into classroom in differentiated learning context is suggested to foster teaching quality and students’ performance.